1993
DOI: 10.1007/bf01695889
|View full text |Cite
|
Sign up to set email alerts
|

p 53 gene rearrangements in chronic myelocytic leukemia

Abstract: We performed Southern-blot analysis of the p53 gene in 41 consecutive patients with typical chronic myelocytic leukemia (CML). In two of them, we were able to study cells during both the chronic and the accelerated phases. Only one of the 29 chronic-phase samples had rearrangement of the p53 gene, whereas three of the nine accelerated-phase samples and one of the five patients in blast crisis exhibited rearrangements. Gene deletion was observed in two patients, one in accelerated phase and the other in blast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…During the following decades, efforts from several research groups confirmed these rearrangements, and genomic patterns similar to what we term here as TP53 promoter gain were reported in osteosarcoma and subtypes of soft tissue sarcomas [69]. In parallel, somatic structural variants affecting TP53 were also found in subsets of leukaemia and carcinomas, including chronic myelogenous leukaemia [70][71][72], lung cancer [73], and prostate cancer [74][75][76][77]. Such variants inevitably silence the TP53 gene, but evidence for concomitant gain-of-function or separation-of-function mechanisms through structural variation has not been described.…”
Section: Discussionsupporting
confidence: 71%
“…During the following decades, efforts from several research groups confirmed these rearrangements, and genomic patterns similar to what we term here as TP53 promoter gain were reported in osteosarcoma and subtypes of soft tissue sarcomas [69]. In parallel, somatic structural variants affecting TP53 were also found in subsets of leukaemia and carcinomas, including chronic myelogenous leukaemia [70][71][72], lung cancer [73], and prostate cancer [74][75][76][77]. Such variants inevitably silence the TP53 gene, but evidence for concomitant gain-of-function or separation-of-function mechanisms through structural variation has not been described.…”
Section: Discussionsupporting
confidence: 71%
“…During the following decades, efforts from several research groups confirmed these rearrangements, and genomic patterns similar to what we here term 'TP53 promoter gain' were reported in osteosarcoma and subtypes of soft tissue sarcomas 35 . In parallel, somatic structural variations affecting TP53 were also found in subsets of leukaemia and carcinomas, including chronic myelogenous leukaemia [36][37][38] , lung cancer 39 and prostate cancer [40][41][42][43] . Such variants inevitably silence the TP53 gene, but evidence for concomitant gain-of-function or separation-of-function mechanisms through structural variation has not been described.…”
Section: Discussionmentioning
confidence: 93%
“…In parallel, somatic structural variations affecting TP53 were also found in subsets of leukemias and carcinomas, including chronic myelogenous leukemia [22][23][24] , lung cancer 25 and prostate cancer [26][27][28][29] . Such variants inevitably silence the TP53 gene, but evidence for a concomitant gain-of-function mechanism has not been reported.…”
mentioning
confidence: 93%
“…In blast crisis CML, p53 is genetically inactivated in 30% of cases 2,[65][66][67][68][69][70][71] and, in the remaining 70% of cases, it is possible that increased MDM2 expression 72 may lead to p53 proteasome degradation. It has been shown that wild-type p53 regulates the activity of RNA polymerases I and III, which control the transcription of rRNA and tRNA, respectively.…”
Section: Role Of P53mentioning
confidence: 99%